2018
DOI: 10.1007/s10526-018-9888-2
|View full text |Cite
|
Sign up to set email alerts
|

Constraints in weed biological control: contrasting responses by implementing nations

Abstract: The compilation of papers in this Special Issue (SI) derives from a Symposium at the 25th International Congress of Entomology, in 2016, entitled ''Rise or demise? A global outlook on the future of classical biological weed control''. In the SIopening-paper, a summary of the 5th edition of the world catalogue of weed biocontrol agents and their target weeds provides a comprehensive international perspective. Weed biocontrol implementation is beleaguered by perceptions of risk and restrictive regulatory procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…2, Sect. 2.2), and implementers, there have been an increasing number of innovative and successful projects, allowing South Africa to play a leadership role in the use of biological control in the management of invasive alien plants (Moran and Hoffmann 2015;Schwarzländer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2, Sect. 2.2), and implementers, there have been an increasing number of innovative and successful projects, allowing South Africa to play a leadership role in the use of biological control in the management of invasive alien plants (Moran and Hoffmann 2015;Schwarzländer et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several assessments have indicated that, for a relatively small country, South Africa has made a disproportionate contribution to the development of invasion science. The country has been a pioneer in the field of invasive alien plant biological control and is currently among the leaders, or may even have assumed the mantle of leadership (Moran and Hoffmann 2015;Schwarzländer et al 2018). Currently, South Africa is one of two countries where the practice of invasive alien plant biological control is thriving (the other being New Zealand; Moran and Hoffmann 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent explorations of challenges and constraints of BC in Europe and beyond, mainly identified technical and practical limitations (Barratt et al, 2018;Shaw et al, 2018;Schwarzländer et al, 2018b). Public (including scientific) and policy support is critical for BC implementation (Thomas and Willis, 1998;Ghosheh, 2005;Vurro and Evans, 2008).…”
Section: Introductionmentioning
confidence: 99%